2013
DOI: 10.1103/physrevc.87.044302
|View full text |Cite
|
Sign up to set email alerts
|

Odd-Jpairing in nuclei

Abstract: We point out a simplicity that arises when we use an interaction in which only an energy with odd J is non-zero. The emphasis is on J = Jmax and in particular J = 9 + in the g 9/2 shell. It is noted that high overlaps can be deceptive. In many cases a single set of unitary 9-j coefficients gives either an exact or a very good approximation to the wave function of a non-degenerate state. The many degeneracies that occur in these calculations are discussed and explained.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 14 publications
2
42
0
Order By: Relevance
“…As was noted in [1] at first glance U (2, j) seems to fall of exponentially with j. This suggests a form Ae −αj (2) For this form ln(|U (2, j)|) = ln(A) − αj.…”
Section: Calculation 21 Asymptotes Of Small Imentioning
confidence: 93%
See 3 more Smart Citations
“…As was noted in [1] at first glance U (2, j) seems to fall of exponentially with j. This suggests a form Ae −αj (2) For this form ln(|U (2, j)|) = ln(A) − αj.…”
Section: Calculation 21 Asymptotes Of Small Imentioning
confidence: 93%
“…In previous works [1,2] Zamick and Escuderos addressed the problem of maximum j-pairing. In the course of these studies they found that results simplified by the fact that a certain coupling matrix element was very small.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the references already mentioned, we add Refs. [11]- [17]. Also, to a large extent, one can regard earlier studies of properties in the f 7/2 shell as precursors to analogous studies in the g 9/2 shell.…”
Section: Comparison Of Shell Model Occupancies With Different Inmentioning
confidence: 99%